The Influence of Intellectual Capital on Firm Value with Financial Performance as an Intervening Variable in High-Ic . Companies: Pengaruh Intellectual Capital Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Intervening pada Perusahaan High-Ic - Amalia, Anggun; Hermawan, Sigit (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of intellectual capital on firm value with financial performance as an intervening variable. The variables used in this study are Intellectual Capital (X1) as measured by VAIC, Firm Value (Y) as measured by Tobins Q and Financial Performance (Z) as measured by ROE. This research includes associative quantitative research. The data in this study is secondary data. The population in this study are Healthcare Industry companiesxlisted on thexStock Exchange inx2014-2019. The samplingxtechnique used was purposivexsampling. The analytical technique usedxin this studyxuses the Partial LeastxSquare (PLS) technique. The resultsxin this study show that IC has an effect on the Financial Performance of Healthcare Industry companies. IC affects the value of pharmaceutical companies in the Healthcare Industry. Financial Performance has no effect on the Healthcare Industry Company Value. Financial Performance can not mediate the relationship between IC and Healthcare Industry Company Value.